Fluorogenic Probes/Inhibitors of β‐Lactamase and their Applications in Drug‐Resistant Bacteria. Issue 1 (18th August 2020) - Ding, Yang; Li, Zheng; Xu, Chenchen; Qin, Wenjing; Wu, Qiong; Wang, Xuchun; Cheng, Xiamin; Li, Lin; Huang, Wei
Abstract: β‐Lactam antibiotics are generally perceived as one of the greatest inventions of the 20 th century, and these small molecular compounds have saved millions of lives. However, upon clinical application of antibiotics, the β‐lactamase secreted by pathogenic bacteria can lead to the gradual development of drug resistance. β‐Lactamase is a hydrolase that can efficiently hydrolyze and destroy β‐lactam antibiotics. It develops and spreads rapidly in pathogens, and the drug‐resistant bacteria pose a severe threat to human health and development. As a result, detecting and inhibiting the activities of β‐lactamase are of great value for the rational use of antibiotics and the treatment of infectious diseases. At present, many specific detection methods and inhibitors of β‐lactamase have been developed and applied in clinical practice. In this Minireview, we describe the resistance mechanism of bacteria producing β‐lactamase and further summarize the fluorogenic probes, inhibitors of β‐lactamase, and their applications in the treatment of infectious diseases. It may be valuable to design fluorogenic probes with improved selectivity, sensitivity, and effectiveness to further identify the inhibitors for β‐lactamases and eventually overcome bacterial resistance. Abstract : This Minireview describes the resistance mechanism of bacteria producing β‐lactamase and further summarize the fluorogenic probes/inhibitors of β‐lactamase, and their applications in the treatment of infectious diseases. We provide guidelines for the design of fluorogenic probes with improved selectivity/sensitivity/effectiveness to identify further inhibitors for β‐lactamases and eventually overcome bacterial resistance.